Georadar tra archeologia ed investigazioni forensi - Barone, Pier Matteo; Ferrara, Carlotta (Archeomatica, 2017)
Destructive tests are no longer a suitable tool for investigations of archeological and cultural heritage monuments. Geophysical surveying like GPR (Ground Penetrating Radar) may represent the only effective and non-destructive technique for recovering and understanding archeological data, pursuing archaeological research and caring for cultural heritage sites. During recent years, the same geophysical approach helps also law enforcement. Progressively it has acquired credibility in the field of non-destructive shallow subsurface forensic investigations. The major benefits of this geophysical technique are the real-time visualization of the data acquired and the quick data acquisition.